Evaluation of a new sink design incorporating ozonated water. Issue 4 (April 2020) - Cooper, J.; Himaras, Y.; Wong, T.; Bryce, E.
SUMMARY: Background: Novel sink and U-trap designs have been developed to reduce contamination by users and diminish biofilm. Real-world experience with new sink designs and adjunctive measures such as ozone has been limited. Aims: To assess a new sink design for splashback and to evaluate the ozonated water feature for reduction of microbial bioburden. Methods: A portable sink unit was created that permitted the application of white absorbent paper to plexiglass shields beside and behind the sink. Participants, wearing painter coveralls and masks, spread 30 mL of tempera paint over their hands and washed for 20 s with neutral soap. Each participant repeated this five times sequentially, and cumulative results were recorded. Escherichia coli was exposed to ozonated water from the sink unit and to regular tap water and evaluated for microbial survival. Findings: Compared with a conventional sink, the SmartFLO3 sink had less environmental contamination within the sink, surrounding area and splashback on to the participant. Despite modifications to enhance ozone generation, readings of reactive oxygen species did not exceed 0.3 ppm, and no significant bactericidal effect was demonstrated. Conclusions: The SmartFLO3 sink reduces splashback and has the potential to reduce pathogen transmission from sinks. At the low levels of ozone generated in this study, no clear bacterial killing effect was observed compared with tap water alone.